2005
DOI: 10.1309/btln5wtmj3pcnrrc
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Protein Tyrosine Kinases in Head and Neck Squamous Cell Carcinomas

Abstract: Protein tyrosine kinases (TKs) are overexpressed in many carcinomas and sarcomas. We studied the expression of the following TKs in head and neck squamous cell carcinoma (HNSCC): platelet-derived growth factor receptor (PDGFR), c-kit, epidermal growth factor receptor (EGFR), and a serine-threonine kinase, Akt. Formalin-fixed, paraffin-embedded tumor blocks from 44 consecutive patients with primary HNSCC and 5 specimens of benign pharyngeal and laryngeal mucosa were retrieved for immunohistochemical analysis. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(50 citation statements)
references
References 17 publications
3
47
0
Order By: Relevance
“…Five years ago the first study analyzing the expression of c-kit in HNSCC was reported. Ongkeko et al described a significantly higher expression of c-kit in HNSCC compared to benign samples (17). Imatinib was originally designed to inhibit a certain tyrosine kinase in CML (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Five years ago the first study analyzing the expression of c-kit in HNSCC was reported. Ongkeko et al described a significantly higher expression of c-kit in HNSCC compared to benign samples (17). Imatinib was originally designed to inhibit a certain tyrosine kinase in CML (10).…”
Section: Discussionmentioning
confidence: 99%
“…The authors described a significantly higher expression of c-kit in HNSCC compared to benign samples. Surprisingly the expression of c-kit was significantly elevated in carcinomas of the pharynx compared to carcinomas of the larynx (17), but also over 90% of the adenoid cystic carcinomas of the head and neck are c-kit positive. The treatment of adenoid cystic carcinoma primary cultures with imatinib showed a down-regulation of c-kit expression and growth-inhibition (18).…”
Section: Protein-tyrosine Kinases (Ptk)mentioning
confidence: 91%
“…Additionally, the practical feedback for extracellular validation was obtained as significant structural indices of polysaccharide components (Tables 1 and 4). On the other hand, the overexpressed performance of some kinases, such as tyrosine protein kinase, is based on the stability of either a de novo managing system [29] or a cellular damage bioplatform [30] and can maintain metabolic balance over an entire process of closed WSMB (Table 2). Furthermore, in order to support the cellular differentiation based on the long-term cultivation bioprocess, the pentose phosphate pathway, e.g., ribose 5-phosphate isomerase, may be activated rather than lignocellulolytic cascades in spite of ligninolytic maximization.…”
Section: Proteomic Evaluation Of Advanced Wsmb Biosystem: Nonspecificmentioning
confidence: 99%
“…Furthermore literature reports an overexpression of EGFR in 38 -80 % of investigated tumors (Grandis & Tweardy 1993;Ongkeko et al 2005;Bei et al 2004). We noted an overexpression of EGFR mRNA and protein (1.5 fold expression was categorized as an overexpression as compared to NOK) in 48 percent of our cell lines.…”
Section: Paper IImentioning
confidence: 99%